AdipoRon Protects against Tubular Injury in Diabetic Nephropathy by Inhibiting Endoplasmic Reticulum Stress. (7th August 2020) - Xiong, Shan; Han, Yachun; Gao, Peng; Zhao, Hao; Jiang, Na; Sun, Lin
Abstract : Endoplasmic reticulum (ER) stress has been reported to play a pivotal role in diabetic nephropathy (DN). AdipoRon is a newly developed adiponectin receptor agonist that provides beneficial effects for diabetic mice; however, its underlying mechanism remains to be delineated. Here, we demonstrated increased expression levels of ER stress markers, accompanied by upregulated levels of proinflammatory cytokines and increased expression of collagen I, fibronectin, Bax, and cleaved caspase 3 in the kidneys of db/db mice compared with control mice. Decreased expression of adiponectin receptor 1 (AdipoR1) and phosphorylated 5 ′ AMP-activated kinase (p-AMPK) was also observed in the kidneys of db/db mice. However, these alterations were partially reversed by intragastric gavage with AdipoRon. In vitro, AdipoRon alleviated high-glucose-induced ER stress, oxidative stress, and apoptosis in HK-2 cells, a human tubular cell line. Moreover, AdipoRon restored the expression of AdipoR1 and p-AMPK in HK-2 cells exposed to high-glucose conditions. Additionally, these effects were partially abrogated by pretreatment with AdipoR1 siRNA, but this abrogation was ameliorated by cotreatment with AICAR, an AMPK activator. Furthermore, the effects of AdipoRon were also partially abolished by cotreatment with compound C. Together, these results suggest that AdipoRon exerts favorable effects on diabetes-induced tubular injury in DN by inhibiting ER stress mediated by the AdipoR1/p-AMPK pathway.